PENGARUH PENGGUNAAN PIL KB YANG MENGANDUNG LEVONORGESTREL DAN LYNESTRENOL TERHADAP POLA PERDARAHAN PADA IBU MENYUSUI - , DIAN ROSDIANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Contraception methods for postpartum and breastfeeding women was still very limited. Progesterone-Only Pill (POP) is one ideal for them. Levonorgestrel (LNG) and Lynesterol is a progesterone derivative. Discontinuation of POP was mostly due to bleeding pattern disturbance. By knowing this effect, POP was expected to be produced in the country and can be the national family planning programs. Objective: Determine the effect of the use of contraception pills containing LNG and Lynesterol to bleeding patterns in breastfeeding women. Method: The study is a double blind block randomized controlled trial for the treatment group (the group given LNG or Lynestrenol pills) and non-randomized controlled trial for the control (IUD acceptors group) to mothers 6-8 weeks postpartum, 20-35 years, and breastfeeding. Follow up was done until the baby is 6 months old. At each follow-up visits we perform physical examination, checking and giving pills and daily cards. Bivariable analysis was by survival analysis and 2 and multivariable was by Cox Proportional Hazard with Time Varying Covariate. The results: 107 women were included with drop-out rate of 17.8%. Most of 32 years, multiparous, ever used contraception with birth spacing of > 60 months. Most complaints were spotting. Amenorrhea has the common pattern. LNG pill users, participant with BMI 18.5 kg/m2, who arenât compliant and non exclusively breastfeeding resume menstruation faster. p results was not meaningful. Conclusion: LNG cause bleeding/menstrual resumption faster in breatfeeding women than Lynestrenol. Body mass index, compliance in taking the pill and breastfeeding status were not statistically significant.